Aspirations for a mass political party in prewar imperial Japan: Conflicting visions of national mobilization - Grover, Bruce; Bandeira, Egas Moniz (Parties as Governments in Eurasia, 1913–1991, 2022)
Amidst the rising militarism of the 1930s, the power of Japanese political parties declined. Yet, they managed to maintain a foothold on power, and the Imperial Rule Assistance Association (IRAA; Taisei yokusankai 大政翼賛会), established in 1940, never quite became a mass political party. The chapter discusses the ultimately frustrated aspirations for the creation of a mass political party in the Japan of the 1930s and the 1940s, focusing on the thought and action of two networks which facilitated the trajectory of the IRAA: The “Alliance for a New Japan” (Shin Nihon dōmei 新日本同盟), a group consisting of some of Japan's most important bureaucrats, and the writings of the magazine Ishin 維新 (“Restoration”), which brought together many reform-minded military officers. The chapter shows that, while they did not put the role of the parliament as such into question, the focus of these thinkers lay on representing the “will of the people” through the Diet beyond liberal party politics. This transformation among important networks envisioned a transformation beginning primarily with a preparation of the mentality of the people through though guidance. Despite the apparent anomaly of the Japanese case in the late 1930s and 1940s, the history of IRAA in Japan was, thus, firmly part of a global trend toward a reconstruction of political systems. The IRAA was in large part a culmination of efforts at social transformation to create a form of political integration of the nation beyond liberal democracy and yet, nevertheless, sought active participation from all segments of society.<br
CRIS-Team Scopus Importer:2022-09-30

Between Chaos and Liberty: Chinese Uses of the French Revolution of 1789 - Bender De Moniz Bandeira, Egas Bernard (Alternative Representations of the Past: The Politics of History in Modern China, 2020)
This chapter traces the trajectory of one of the most emblematic events of modern history, the French Revolution of 1789, in Chinese political debates from late Qing to contemporary times. It shows that the French Revolution has been appropriated and used by Chinese actors—intellectuals, politicians, students, and others—in the light of their own historical experiences and for widely varying discursive objectives. It has been referenced in China both for the ideals it espoused and for the bloodshed and instability that it brought about in late 18th century France. Thus, it has not only served as an inspiration and a point of comparison for China’s own revolutions, chiefly the republican revolution of 1911, or as a democratic inspiration for Chinese intellectuals. Representations of the French revolution as an event of chaos and brutality have just as often been used by revolutionists to search for more suitable revolutionary models, as well as by conservative intellectuals and governments to debate reforms designed to prevent instability and political strife. Ultimately, the chapter shows that landmark events such as the French Revolution are far from being exclusive memories of the West. Rather, their diverse Chinese uses have become local refractions of global elements of collective memory.

China and the Concomitant Political Upheavals in Russia, Turkey and Persia: Non-Western Influences on Constitutional Thinking in Late Imperial China (1893-1911) - Bender De Moniz Bandeira, Egas Bernard (Transcultural studies, 2017)
Research about Sino-foreign cultural interactions during the last decades of the Qing Empire pays much attention to the extremely dense and complex relations between Japan and China. Against this backdrop, historians have tended to neglect that the Chinese “constitutional preparation” of the years 1905-06 was concomitant to the promulgation of constitutional documents in other thitherto absolutist countries such as Russia, the Ottoman Empire and Persia. This paper shows that, during the whole period of “constitutional preparation”, the Qing government, media and intellectuals remained well aware of these events. In particular, the experiences made by countries similar to China did not fail to have a manifold impact on Chinese perceptions on how to cope with China’s own challenge. On the one hand, the international trend fostered the feeling that a constitutional document was needed for purposes of internal and external legitimacy, and for building nationalism from above. On the other hand, the fact that the hastily introduced constitutions in these countries did not necessarily solve their underlying problems was noticed as well. Describing them as mere “sham constitutions” was one possible interpretation, but they also reinforced Chinese notions that the population at large was not yet ripe for partaking in the political reforms and that thorough “preparation” was needed firs
Keywords: Constitutionalism; Sino-Russian relations; Conceptual Globalisation; Translations; Kitaoni Saburō

Creating a Constitutional Absolute Monarchy: Li Jiaju, Dashou, and Late Qing Interpretations of the Japanese Parliament - Bender De Moniz Bandeira, Egas Bernard (International History Review, 2022)
This paper explores interpretations of the Japanese parliament by governmental actors in the Qing empire, most importantly the commissioners for constitutional research Li Jiaju 李家駒 (1871–1938) and Dashou 達壽 (1870–1939). It shows that, within a theoretical framework formed in dialogue with their Japanese constitutionalist colleagues, these actors came to understand the Japanese parliament as an organ possessing tightly limited attributions gifted by the emperor. They maintained that the constitutional system should not be parliamentary, although the parliament was one of its necessary elements. Rather, it should be based on an imperially authorised constitutional document and a form of government centred on the figure of the emperor, in which the parliament would play a consultative rather than legislative role. Ultimately, the article shows that, within a Eurasia-wide wave of imperial transformation in which officials envisioned parliaments mainly as organs designed to increase governmental efficiency, political actors like Li Jiaju and Dashou creatively adapted categories of political science to their own political needs.<br

East Asian Uses of Indian Epic Literature: Refractions of the Mahabharata in Japan and China, Late Nineteenth–Early Twentieth Century - Bender De Moniz Bandeira, Egas Bernard (The Mahabharata in Global Political and Social Thought, 2024)
Introduction In 1909, the Sino-Japanese poet Su Manshu painted an image of Cai Yan (Lady Wenji), a poetess of the late second century who had spent 12 years in captivity abroad before returning to the Han Empire, and sent it to his friend, the art collector Liu Jiping (also known as Liu San). Liu wrote a series of poems to appreciate Su's gift, including the following verses: Why would a Chinese literatus at the turn of the twentieth century write a poem mentioning the Indian epic Mahabharata to match a seemingly unrelated painting? Until well into the twentieth century, the name of the Mahabharata had been mostly unknown in East Asia, except for a few isolated references in Buddhist texts. Against the sheer preponderance of Buddhist thought in the intellectual flows between India and China, it might even have seemed futile to look for an East Asian reception of the Mahabharata. Yet, over the centuries, various elements related to the Mahabharata circulated between South Asia and East Asia and played significant roles within East Asian culture itself. By the late nineteenth and early twentieth centuries, Indian thought continued to play a major role in East Asia amidst intense contact between China, Japan, Europe, and India itself. In close interdependence with the notion of the ‘West’, the category of ‘Asia’ emerged in the Japanese and Chinese imaginary by the turn of the twentieth century, when intellectuals developed a globalized sense of their position in the world. India became a renewed object of study but, at the same time, also a ‘method’ to deal with the challenges posed by modernity. Interest in India and its role within ‘Asia’ was a significant element not only in understanding the geopolitical realities and ‘catching up’ with the ‘West,’ but also in the quest for a ‘world beyond the material and epistemological constraints’ posed by Western modernity. While Buddhism still played a crucial role as the connecting bond between the two macroregions of East Asia and South Asia, some intellectuals came to understand it in a wider framework that also encompassed other traditions such as that of the Mahabharat

From dynastic cycle to eternal dynasty: The Japanese notion of unbroken lineage in Chinese and Korean constitutionalist debates, 1890–1911 - Moniz Bandeira, Egas (Global Intellectual History, 2022)
This paper shows that the poltical and social upheavals of the late nineteenth and early twentieth century in East Asia also engendered novel ideas and cross-national debates about dynasties in East Asia. The Japanese notion of a ‘line of Emperors unbroken for ages eternal’ became the most emblematic provision of the Meiji Constitution. Under the impact of the Japanese model and of modern discourses on constitutional law, the Qing and Korean governments sought to radically transform traditional concepts of dynastic rule by constitutionally perpetuating the ruling dynasties. However, the notion of an unbroken lineage proved to be highly ambiguous outside of the Japanese context. Its adoption in the Qing constitutional outline of 1908 met with considerable resistance and nurtured suspicions that ‘constitutional preparation’ was only serving the Court's selfish interests. But under the surface, the Japanese model of an unbroken ruling dynasty was de-dynasticised and applied to the notion of constitution and even to the State itself. As the Confucian classics were no longer sufficient to legitimise rulership, the new notion of an eternal fundamental law fused with traditional notions of permanent principles of governance and helped establishing written constitutional charters as ineluctable elements of the modern nation-state in East Asia.
Created from Fastlane, Scopus look-up
Keywords: bansei ikkei; constitutions; Dynasties; Qinding xianfa dagang; Taehan’guk kukche

Globalgeschichten aus China–Aktuelle Debatten in der Volksrepublik - Matten, Marc; Bender De Moniz Bandeira, Egas Bernard (Campus, 2023)
Wie rezipieren chinesische Historikerinnen und Historiker globalgeschichtliche Ansätze aus Nordamerika und Europa? Mit neun ausführlich kommentierten Texten parteinaher und -ferner Gelehrter mit und ohne Forschungserfahrung im Ausland, die hier erstmals in deutscher Übersetzung vorliegen, bietet dieser Band eine konzise Einführung in aktuelle Debatten zur Globalgeschichte in der Volksrepublik China. Die Breite der Stimmen reicht von der Kritik am Eurozentrismus globalgeschichtlicher Ansätze bis zu ihrem Beitrag für die Reinterpretation der chinesischen Geschichte seit Beginn der Globalisierung. Deutlich werden das Spannungsverhältnis von National- und Globalgeschichte, die Sorge um eine Verwestlichung der chinesischen Geisteswissenschaften, aber auch das Bemühen, chinesische Begrifflichkeiten für die Weiterentwicklung der Disziplin zu formuliere

Introduction - Sablina, Ivan; Bender De Moniz Bandeira, Egas Bernard (Parliaments, Elections and Constitutions in Qing and Russian Imperial Transformations, 1860s-1920s, 2022)
This special issue explores concepts and practices related to parliamentarism in the imperial and post-imperial transformations of the Qing and Russian Empires, as well as their successor states. It demonstrates that representative institutions were a crucial factor in the establishment of modernized empires or post-imperial states. In particular, the issue explores how the ‘mining’ of own imperial past and present for concepts and practices was used in combination with the globally circulating forms of representation in the development of parliamentary institutions, how particular interest groups defined through ethnicity, region, religion, or class were represented, and, ultimately, how the parliamentary developments informed the formation of single-party regimes in the post-imperial settings.<br
Keywords: Russia; China; Qing; Soviet; parliament; diversity

Introduction - Sablin, Ivan; Bandeira, Egas Moniz (Parliaments, Estates and Representation, 2022)
This special issue explores concepts and practices related to parliamentarism in the imperial and post-imperial transformations of the Qing and Russian Empires, as well as their successor states. It demonstrates that representative institutions were a crucial factor in the establishment of modernized empires or post-imperial states. In particular, the issue explores how the ‘mining’ of own imperial past and present for concepts and practices was used in combination with the globally circulating forms of representation in the development of parliamentary institutions, how particular interest groups defined through ethnicity, region, religion, or class were represented, and, ultimately, how the parliamentary developments informed the formation of single-party regimes in the post-imperial settings.<br
Keywords: Russia; China; Qing; Soviet; parliament; diversity

Introduction: Parties from vanguards to governments - Sablin, Ivan; Bandeira, Egas Moniz (Parties as Governments in Eurasia, 1913–1991, 2022)
CRIS-Team Scopus Importer:2022-09-30

Late Qing parliamentarism and the borderlands of the Qing Empire—Mongolia, Tibet, and Xinjiang (1906–1911) - Moniz Bandeira, Egas (Journal of Eurasian Studies, 2020)
The article examines the relationship between the late Qing constitutional movement of 1905–1911 and the vast borderland regions of the Qing Empire–that is, Mongolia, Tibet, and Xinjiang. It traces how intellectuals and officials concerned with devising constitutional policies foresaw the integration of these regions into the nascent parliamentary institutions at the provincial and central levels. The article argues that the status of the borderlands played a significant role in late Qing constitutional debates, and that debates on borderland constitutionalism were a phenomenon of a wider constitutional wave affecting Eurasia in the 1900s. Chinese intellectuals and officials felt the competition of the emerging parliamentary institutions in Russia and the Ottoman Empire, and anticipating that constitutional and parliamentarist movements among Mongols, Tibetans, and Turki could lead to the separation of the respective regions, they hoped that parliamentary representation, albeit limited, would be an instrument against centrifugal tendencies on the borders. Hence, they called for constitutional reforms in China and for the inclusion of the borderland populations into the new parliamentary institutions. Yet, arguing with the sparse population of the borderlands as well as with their alleged economic and cultural backwardness, they denied the direct application of the constitutional plan to these territories. The differentiated policies eventually applied to the borderlands were a lackluster compromise between these conflicting interests.
Keywords: Constitutional history of China; history of Mongolia; history of Xinjiang; imperialism; Late Qing History; parliamentarism in China; Political Consultative Council (Zizhengyuan)

Montesquieu vs. Bagehot: Two Visions of Parliamentarism in Japan - Bender De Moniz Bandeira, Egas Bernard (2021)
This chapter focuses on the Tokugawa-Meiji transition period in the Japanese archipelago. It discusses the question of the perceived poor prospects for the transplantation of a "parliament" onto Japanese soil. The Japanese system itself, on which the new parliament was premised, hovered between a centralized unitary state and an extremely decentralized federal state (at the time, the controversy was conceptualized by means of the Confucian terms hōken 封建 and gunken 郡県). This polarization of the image of the existing Japanese system as the basis of the new parliament naturally produced a polarization of the image of the congress as well, namely between the decentralized “Montesquieu Model” and the centralized “Bagehot Model.” I want to show that the story of modern Japanese parliamentarism was never a monolithic success story, but rather a drama of conflicts that was open to different possibilitie

O advento do Constitucionalismo na China - Moniz Bandeira, Egas (Ballot, 2016)
No século XIX e no início do século XX, o constitucionalismo era uma tendência mundial, não só na Europa e nas Américas, como também na Ásia: O Japão outorgou uma constituição em 1889/90, a Coréia, em 1899, e a Pérsia, em 1906. O governo chinês anunciou a sua intenção de outorgar uma constituição em 1906, mas a dinastia imperial foi forçada a abdicar em 1912 sem haver promulgado uma carta constitucional definitiva. O presente artigo apresenta essa primeira tentativa de introdução do constitucionalismo na China como reação a fatores internos e externos. Ao mesmo tempo que a constituição era uma nova forma de legitimar-se internamente, ela trazia vantagens no cenário internacional. A experiência chinesa mostra que, mesmo que superficial, ter uma forma constitucional de governo estava a tornar-se um dos elementos definidores do Estado na ordem mundial emergente.

Parliamentary options for a multi-ethnic state: sovereignty, frontier governance, and representation in early twentieth-century China - Bender De Moniz Bandeira, Egas Bernard (Parliaments, Estates and Representation, 2022)
This article reconstructs two modes of parliamentary representation of (post-)imperial diversity in early twentieth-century China. One model foresaw a differentiated representation of the borderlands in the nascent parliamentary institutions, using upper house seats to garner loyalty from the nobility at the same time as it denied electoral participation. The second model stipulated electoral equality between the borderland regions and the inner provinces. While the first model parliamentarized imperial forms of governance, it was also informed by and partially conformed to global models of governance. The second was informed by notions of undivided national sovereignty. In the late Qing Empire, the government decided against the second model, for it was deemed to presuppose a degree of national integration not given in the Empire. The challenges posed by the proclamation of the Republic of China, in particular the declarations of independence of Mongolia and Tibet, led to a strong emphasis on the newly-founded state’s unity and the swift adoption of the second model. This choice, however, was neither uncontested nor was its implementation complete.
CRIS-Team Scopus Importer:2022-04-22
Keywords: borderlands; Canyiyuan (Senate); Mongolia; parliamentarism; Qing Empire; Republic of China

Parties as Governments in Eurasia, 1913–1991 - Sablina, Ivan; Bender De Moniz Bandeira, Egas Bernard (2022)
This book examines the political parties which emerged on the territories of the former Ottoman, Qing, Russian, and Habsburg empires and not only took over government power but merged with government itself. It discusses how these parties, disillusioned with previous constitutional and parliamentary reforms, justified their takeovers with programs of controlled or supervised economic and social development, including acting as the mediators between the various social and ethnic groups in the respective territories. It pays special attention to nation-building through the party, to institutions (both constitutional and de facto), and to the global and comparative aspects of one-party regimes. It explores the origins of one-party regimes in China, Czechoslovakia, Korea, the Soviet Union, Turkey, Yugoslavia, and beyond, the roles of socialism and nationalism in the parties’ approaches to development and state-building, as well the pedagogical aspirations of the ruling elites. Hence, by revisiting the dynamics of the transition from the earlier imperial formations via constitutionalism to one-party governments, and by assessing the internal and external dynamics of one-party regimes after their establishment, the book more precisely locates this type of regime within the contemporary world’s political landscape. Moreover, it emphasises that one-party regimes thrived on both sides of the Cold War and in some of the non-aligned states, and that although some state socialist one-party regimes collapsed in 1989–1991, in other places historically dominant parties and new parties have continue.<br

The 22 Frimaire of Yuan Shikai: Privy councils in the constitutional architectures of Japan and China (1887–1917) - Bender De Moniz Bandeira, Egas Bernard (Planting Parliaments in Eurasia, 1850–1950: Concepts, Practices, and Mythologies., 2021)
Privy councils are among the most traditional, yet least conspicuous forms of collective decision-making in modern states. However, using the example of East Asia, this chapter shows that, far from being a moribund relic of the pre-constitutional past, advisory councils to the head of state were a highly productive global element of constitution-building which was variously adapted according to local needs and conditions. The architecture of the Napoleonic Constitution of 22 Frimaire, which complemented the executive ministers of state with an additional Council of State and came to be underpinned by the idea of a “neutral” or “moderating” branch of government, promised attractive advantages to the makers of East Asia’s first modern constitutions. The Japanese Privy Council (Sūmitsuin) alleviated the dangers of putting too much power into the hands of the Emperor, while also securing the power of the ruling oligarchy in a context of mistrust of the legislative branch. The Sūmitsuin served as a model for both the Qing Empire and the Republic of China, although the political objectives attached to the respective advisory councils diverged significantly. Eventually, both in Japan and in China, the institution was abolished when it had become too closely connected with authoritarian politics.

The Late Qing Constitutional Movement in the Global Constitutional Moment of the 1900s - Bandeira, Egas Moniz (Routledge Handbook of Constitutional Law in Greater China, 2022)
The constitutional history of the late Qing Empire is mostly understood as a history of reception, i.e., of how Chinese political and intellectual actors adapted the Japanese model set by the Meiji Constitution of 1889, which in turn was based on various European models, mainly, although not exclusively, of German origin. Accordingly, the official policy of ‘constitutional preparation’ (yubei lixian 預備立憲) instituted in 1906 is interpreted as a belated response to the challenges of Western modernity, which by its conservative nature was at odds with the ‘tide of the time’ (shidai chaoliu 時代潮流).<br

The Secret Joys of a Scholar: A Tribute to Rudolf G. Wagner - Bender De Moniz Bandeira, Egas Bernard (Transcultural studies, 2019)